Handbook of multi-commodity markets and products : structuring, trading and risk management - Roncoroni, Andrea; Fusai, Gianluca; Cummins, Mark, 1968- (John Wiley & Sons Ltd, 2015)
The comprehensive guide to working more effectively within the multi-commodity market. The Handbook of Multi-Commodity Markets and Products is the definitive desktop reference for traders, structurers, and risk managers who wish to broaden their knowledge base. This non-technical yet sophisticated manual covers everything the professional needs to become acquainted with the structure, function, rules, and practices across a wide spectrum of commodity markets. Contributions from a global team of renowned industry experts provide real-world examples for each market, along with tools for analyz.